A CLOSED-FORM GARCH VALUATION MODEL FOR POWER EXCHANGE OPTIONS WITH COUNTERPARTY RISK. Issue 2 (April 2020) - Wang, Xingchun; Xu, Guangli; Li, Dan
Abstract: In this paper, a discrete-time framework is proposed to value power exchange options with counterparty default risk, where counterparty risk is considered in a reduced-form setting and the variance processes of the underlying assets are captured by GARCH processes. In addition, the proposed model allows for the correlation between the intensity of default and the variances of the underlying assets by breaking down the total risk into systematic and idiosyncratic components. By dint of measure-change techniques and characteristic functions, we obtain the closed-form pricing formula for the value of power exchange options with counterparty default risk. Finally, numerical results are presented to show the power exchange option values.